SURVEI MANAJEMEN EKSTRAKURIKULER FUTSAL SMP NEGERI 4 SIDOARJO - AKHMADI, TRI (Jurnal Pendidikan Olahraga dan Kesehatan, 2013)
Abstract                                                               Activites Extracurricular at school is aplace to accommodate the interests and talents possessed by students both in the fields of art science, social, cultural, religious, sport and others. Many extracurricular activities that can be fllowed by students in school extracurricular activities include soccer, futsal extracurricular, basket ball, volley ball, badminton, karate, dance and much more. Junior high school 4 Sidoarjo is one school that is able to develop good sporting extracurricular activities, one of which  is extracuriculer futsal Ekstracuriculer achievements of Junior high school futsal achieve level  4 Sidoarjo district, municipital and provincial, there fore researchers interested in stadiying management Ekstracuriculer Junior high school 4 Sidoarjo specially in extracuriculer futsal. Junior high school 4 Sidoarjo has good performance in the championship he attended in 2009 include two trophies won sidoarjo Dinas, campion 2 cup Smantig cup and Junior high school 4 Sidoarjo in 2010 sidoarjo able Smanda won 2 cup, 2 sonis cup championand the in 2011 Junior high school 4 Sidoarjo Grabbing a cup of Education Sidoarjo champion, champion 2 tropy Sma 1 Sidoarjo. In this regard, the purpose of this study is basically to findanswer to problems at the Junior high school futsal  Sidoarjo 4 so that in can continue to keep the traditions champions at avery tournament. Bases of the questionnaire which is done, we known the averageof futsal management score from the planning 84,09 %, organitation 60,41 %, implementation 79,03 % and supervising 61,11 %. From this questionnaire test can be concluded that Extracurricular management in Junior high school 4 Sidoarjo, the researcherconlude that Extracurricular management of Junior high school 4 Sidoarjo most of them have done by 73,57 % presentation. Keywords : Management, extrecuricular futsal